Mineralogical Insights to Identify Göktepe Marble in the Sculptural Program of Quinta Das Longas Villa (Lusitania) - M. Pilar Lapuente Mercadal (MDPI AG, 2021)
This archaeometric study is focused on the marble used in a group of fragmented sculptures found at the Roman villa of Quinta das Longas (Elvas, Portugal). Dating from the 4th century AD, the pieces are of remarkable quality and correspond to ideal and mythological figures from several iconographic cycles. The numerous fragments, all of very fine-grained white marble, are associated with the ornamentation of an impressive nymphaeum of the villa. Their high level of sculpture technique and style, the models followed and their similar typology to other well-known parallels raise the hypothesis of being linked with Aphrodisian workshops. Using a well-established multi-method approach, with Optical microscopy, X-ray Powder Diffraction (XRPD), qualitative and quantitative cathodoluminescence (CL) by CL-Optical and CL-SEM, and stable C and O isotopic and trace element analytical techniques (IRMS and ICP-AES), together with complementary parameters obtained from electron paramagnetic resonance (EPR) and 87Sr/86Sr isotopes, the marble provenance can be identified with certainty. The results all point to the best quality of white Göktepe marble, confirming the stylistic connection to the ancient Carian sculptors.